Working and Long-Term Memory Deficits in Schizophrenia: Is There a Common Prefrontal Mechanism? - Barch, Deanna M.; Csernansky, John G.; Conturo, Tom (Journal of Abnormal Psychology, 2002)
This study tested the hypothesis that dorsolateral prefrontal cortex deficits contribute to both working memory and long-term memory disturbances in schizophrenia. It also examined whether such deficits were more severe for verbal than nonverbal stimuli. Functional magnetic resonance imaging was used to assess cortical activation during performance of verbal and nonverbal versions of a working memory task and both encoding and recognition tasks in 38 individuals with schizophrenia and 48 healthy controls. Performance of both working memory and long-term memory tasks revealed disturbed dorsolateral prefrontal cortex activation in schizophrenia, although medial temporal deficits were also present. Some evidence was found for more severe cognitive and functional deficits with verbal than nonverbal stimuli, although these results were mixed. Reprinted by permission of the publisher.